2016
DOI: 10.1124/jpet.116.233924
|View full text |Cite
|
Sign up to set email alerts
|

Task- and Treatment Length-Dependent Effects of Vortioxetine on Scopolamine-Induced Cognitive Dysfunction and Hippocampal Extracellular Acetylcholine in Rats

Abstract: Major depressive disorder (MDD) is a common psychiatric disorder that often features impairments in cognitive function, and these cognitive symptoms can be important determinants of functional ability. Vortioxetine is a multimodal antidepressant that may improve some aspects of cognitive function in patients with MDD, including attention, processing speed, executive function, and memory. However, the cause of these effects is unclear, and there are several competing theories on the underlying mechanism, notabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 49 publications
3
21
0
Order By: Relevance
“…However, a recent paper from this laboratory investigated the effects of vortioxetine in another model of attention, visual signal detection task (VSDT) impairments induced by the muscarinic acetylcholinergic receptor antagonist scopolamine. This study demonstrated that, although acute vortioxetine treatment was able to reverse scopolamine-induced deficits in memory performance at clinically relevant doses, it was unable to alter scopolamine-induced impairments in the VSDT ( Pehrson et al, 2016a ). Importantly, acute administration of the acetylcholinesterase inhibitor donepezil was able to significantly attenuate scopolamine-induced VSDT impairments in this study ( Pehrson et al, 2016a ).…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…However, a recent paper from this laboratory investigated the effects of vortioxetine in another model of attention, visual signal detection task (VSDT) impairments induced by the muscarinic acetylcholinergic receptor antagonist scopolamine. This study demonstrated that, although acute vortioxetine treatment was able to reverse scopolamine-induced deficits in memory performance at clinically relevant doses, it was unable to alter scopolamine-induced impairments in the VSDT ( Pehrson et al, 2016a ). Importantly, acute administration of the acetylcholinesterase inhibitor donepezil was able to significantly attenuate scopolamine-induced VSDT impairments in this study ( Pehrson et al, 2016a ).…”
Section: Introductionmentioning
confidence: 79%
“…This study demonstrated that, although acute vortioxetine treatment was able to reverse scopolamine-induced deficits in memory performance at clinically relevant doses, it was unable to alter scopolamine-induced impairments in the VSDT ( Pehrson et al, 2016a ). Importantly, acute administration of the acetylcholinesterase inhibitor donepezil was able to significantly attenuate scopolamine-induced VSDT impairments in this study ( Pehrson et al, 2016a ). As an assessment of vortioxetine’s general effects on attention function, this study could be questioned based on the use of scopolamine as a platform for inducing attention impairment.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations